2013
DOI: 10.3233/bmr-130404
|View full text |Cite
|
Sign up to set email alerts
|

Long latency reflex response of superficial trunk musculature in athletes with chronic low back pain

Abstract: Chronic LBP athletes exhibit a delay in onset latency to Unexpected perturbations and reduced long latency response amplitudes to perturbation tasks compared to asymptomatic athletes. These changes could predispose athletes to recurrent low back pain and further injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
0
18
2
Order By: Relevance
“…Three studies reported increased internal obliquus reflex latencies in patients with LBP (Radebold et al, 2000, 2001; Liebetrau et al, 2013), while one did not (Akbari et al, 2015). Lastly, patients with LBP exhibited significantly longer reflex latencies over the rectus abdominis muscles in a majority of studies (Radebold et al, 2000, 2001; Reeves et al, 2005; Ramprasad et al, 2010; Liebetrau et al, 2013; Shenoy et al, 2013). However, three studies failed to identify differences between LBP patients and controls (Newcomer et al, 2002; Lariviere et al, 2010; Akbari et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Three studies reported increased internal obliquus reflex latencies in patients with LBP (Radebold et al, 2000, 2001; Liebetrau et al, 2013), while one did not (Akbari et al, 2015). Lastly, patients with LBP exhibited significantly longer reflex latencies over the rectus abdominis muscles in a majority of studies (Radebold et al, 2000, 2001; Reeves et al, 2005; Ramprasad et al, 2010; Liebetrau et al, 2013; Shenoy et al, 2013). However, three studies failed to identify differences between LBP patients and controls (Newcomer et al, 2002; Lariviere et al, 2010; Akbari et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…A total of 15 studies investigated the effect of LBP and neuromuscular adaptations following unexpected trunk perturbation (Radebold et al, 2000, 2001; Newcomer et al, 2002; Reeves et al, 2005; Stokes et al, 2006; Lariviere et al, 2010; MacDonald et al, 2010; Ramprasad et al, 2010; Jacobs et al, 2011; Jones et al, 2012a,b; Liebetrau et al, 2013; Shenoy et al, 2013; Gao et al, 2014; Akbari et al, 2015). Among these studies, two recruited participants with acute/episodic LBP (Stokes et al, 2006; Jones et al, 2012b) while all other included participants with chronic LBP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations